2020
DOI: 10.1111/echo.14600
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular diastolic dysfunction in patients with obstructive sleep apnea syndrome

Abstract: Background and Objectives This study aimed to assess right ventricular (RV) diastolic dysfunction in patients with obstructive sleep apnea syndrome (OSAS) using velocity vector imaging (VVI) and to evaluate the application of VVI technology. Methods According to the apnea–hypopnea index (AHI), 69 patients with OSAS were divided into three groups: mild, moderate, and severe. A total of 35 cases of healthy subjects were enrolled as the control group. Digital images of apex four‐chamber views were acquired to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…Li and co-workers also showed that this ventricular dysfunction positively correlated with the degree of OSAS, expressed in terms of apnea hypopnea index (AHI). 1 In other words, increased levels of AHI significantly correlated with an impairment of right ventricular dysfunction. 1 These observations are very clear and in part confirm our previous data, which demonstrated that systolic pulmonary artery pressure (PAP) in obese patients with OSA was significantly higher than in obese patients without OSAS (P < .0001), whereas patients with OSAS alone without obesity did not have a statistical significant increase in systolic PAP.…”
Section: Right Ventricular Diastolic Dysfunction Might Correlate Withmentioning
confidence: 98%
See 3 more Smart Citations
“…Li and co-workers also showed that this ventricular dysfunction positively correlated with the degree of OSAS, expressed in terms of apnea hypopnea index (AHI). 1 In other words, increased levels of AHI significantly correlated with an impairment of right ventricular dysfunction. 1 These observations are very clear and in part confirm our previous data, which demonstrated that systolic pulmonary artery pressure (PAP) in obese patients with OSA was significantly higher than in obese patients without OSAS (P < .0001), whereas patients with OSAS alone without obesity did not have a statistical significant increase in systolic PAP.…”
Section: Right Ventricular Diastolic Dysfunction Might Correlate Withmentioning
confidence: 98%
“…1 In other words, increased levels of AHI significantly correlated with an impairment of right ventricular dysfunction. 1 These observations are very clear and in part confirm our previous data, which demonstrated that systolic pulmonary artery pressure (PAP) in obese patients with OSA was significantly higher than in obese patients without OSAS (P < .0001), whereas patients with OSAS alone without obesity did not have a statistical significant increase in systolic PAP. 2 In our opinion, obesity, which often appears earlier than OSAS, starts promoting endothelial pulmonary dysfunction, while the coexistence with OSAS might accelerate the evolution toward pulmonary hypertension.…”
Section: Right Ventricular Diastolic Dysfunction Might Correlate Withmentioning
confidence: 98%
See 2 more Smart Citations
“…1 Therefore, the purpose of our study is to assess the influence of obstructive sleep apnea syndrome (OSAS) on right ventricular (RV) diastolic dysfunction. 2 At the beginning of the study, we have noticed the influence of obesity on pulmonary hypertension.…”
Section: Correlation Between Ahi and Right Ventricular Diastolic Funcmentioning
confidence: 99%